Creating an effective digital channel for sales and promotion of IT services in the B2B segment: the case of Ismet.kz - Duisebayeva, M. (International School of Economics KAZGUU, Nur-Sultan, 2022)
This paper discusses the use of the effectiveness of digital promotion and sales channels in the B2B segment in the Kazakhstan market, which will affect: increase profits, brand promotion, create and strengthen reputation, and also provide support for the interest of regular customers in business. The introduction of a marketplace of IT services for business in Kazakhstan will be in high demand among entrepreneurs. The structure and volume of the thesis: The thesis consists of an introduction, 4 chapters, conclusion and recommendations, a list of references and applications. The text of the master's work includes 6 tables, 15 figures Key words:B2B, promotion, digital marketing, sales, IT B2B - is a term that defines the type of information and economic interaction, classified by the type of interacting subjects, in this case, these are legal entities that work not for the end ordinary consumer, but for the same companies, that is, for another business. (Kotler F., 2018) Sale - the exchange of goods or services for money, confirmed by a sales receipt, an act of work performed, an invoice for the transfer of goods. (Kotler F., 2018) Promotion - a complex of market activities (marketing activities), the goals of which are to increase the share of a product, service, company or brand occupied by them in the market; bringing goods to the market; increasing their recognition; attracting new customers, increasing sales efficiency through a communicative impact on staff, partners and consumers. (marketch.ru, 2021) Digital Marketing- is a generic term used to refer to targeted and interactive marketing of products and services that uses digital technology to attract leads and retain them as consumers. (Akulich M., 2019) IT - processes, methods of searching, collecting, storing, processing, providing, distributing information and ways of implementing such processes and methods. (It.info.ru, 2021)
Keywords: B2B segment, IT services, digital channel